All Days 2012
DOI: 10.2118/160747-ms
|View full text |Cite
|
Sign up to set email alerts
|

Increased Turbo Compressor Reliability by Analysis of Fluid Structure Interaction

Abstract: The integrity of compressors and pumps is of paramount importance for the gas and oil industry. Failures may result in serious production losses that are in no proportion with the cost of the equipment involved. Besides, the equipment may be inaccessible for maintenance for a long period of time due to unfavourable weather conditions. The requirements of compressors with respect to pressures, capacity, power and operating range, are increasing. The answer to this is innovative compressor concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…On the other hand, an individual blade fracture damages adjacent blades or even all impeller blades, resulting in a series of problems such as rotor imbalance, floating bearing, and thrust bearing wear, turbine impeller rubbing against the shell, and finally damage to the whole turbocharger. 2,3 The impeller consists of two parts, including the blades and the hub. It should be indicated that the interaction force and torque are generated between the stationary hub and the rotating blade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, an individual blade fracture damages adjacent blades or even all impeller blades, resulting in a series of problems such as rotor imbalance, floating bearing, and thrust bearing wear, turbine impeller rubbing against the shell, and finally damage to the whole turbocharger. 2,3 The impeller consists of two parts, including the blades and the hub. It should be indicated that the interaction force and torque are generated between the stationary hub and the rotating blade.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the literature indicates that many scholars have conducted extensive investigations about structural parameters and mechanical properties of compressor impellers. Smeulers et al 2 found that the vibration generated by the machine may result in resonance in the compressor impeller. When the resonance occurs, the vortex shedding appears at the blade edge and a relatively large dynamic force is generated at the leading edge of the rim.…”
Section: Introductionmentioning
confidence: 99%